Community power for liveable cities - Marinova, Dora; Hossain, Md Amzad (Henry Stewart Publications, 2014)
With the majority of the world’s population now living in urban environments, the city has started to be representative of a lifestyle that is detached from nature and geared towards a high level of consumption. This paper argues that putting community development first is a key to the move towards a liveable city. A city represents the knowledge, ethics, values and spirituality of its people, and making better communities is a way to make better cities. The focus of the paper is on how to sustain community in the city. It explores the concepts of: (1) self-reliant living; (2) sustainability self-education; (3) self-governance; and (4) community self-organisation as principles underpinning successful communities in urban environments. They not only help to create a sense of place, but also influence the choice of technologies adopted in the city, including transport and infrastructure.